2016
DOI: 10.1111/jsap.12557
|View full text |Cite
|
Sign up to set email alerts
|

Application of xenogeneic anti‐canine distemper virus antibodies in treatment of canine distemper puppies

Abstract: Porcine anti-canine distemper virus antibodies improved survival in puppies affected with canine distemper with minimal adverse effects. Therefore, this therapy could be considered for treatment of endangered animal species infected with canine distemper virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The antibody-mediated passive immunotherapy for CD began in the 1930s [ 41 ]. The clinical practice showed that antiserum or antibody could significantly reduce clinical symptoms and prolong the survival period of the diseased dogs [ 12 , 42 ]. For a long time, the antiserum or antibody used in clinical treatment of canine distemper and canine parvovirus mainly came from dogs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody-mediated passive immunotherapy for CD began in the 1930s [ 41 ]. The clinical practice showed that antiserum or antibody could significantly reduce clinical symptoms and prolong the survival period of the diseased dogs [ 12 , 42 ]. For a long time, the antiserum or antibody used in clinical treatment of canine distemper and canine parvovirus mainly came from dogs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CD has become a common infectious disease in pet clinic [ 11 ]. Due to its excellent therapeutic effect, the most effective anti-CDV drug remains to be CDV antiserum (or antibody) that conveys satisfactory prevention and treatment of CD [ 12 ]. Currently, the antiserum or antibody used to prevent/treat CD was mainly derived from dogs (homologous animals) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2016) used the porcine anti-canine distemper virus IgG and F(ab′) 2 antibody fragments as passive immunotherapy to treat infected puppies exhibiting respiratory signs without neurological signs of distemper and showed that 76% of pups (19 out of 25) survived. However, 8 of 25 (32%) pups showed neurological symptoms during treatment(Liu et al 2016).…”
mentioning
confidence: 99%
“…Canine distemper (CD) is one of the most contagious and fatal diseases affecting all families of carnivores, including dogs and wild raccoons [ 10 , 17 , 29 ]. CDV (family Paramyxoviridae , genus Morbillivirus ) infection is a multisystemic disease affecting the respiratory and gastrointestinal tracts, central nervous system, and various other organs and tissues, and can induce immunosuppression [ 3 , 29 ].…”
mentioning
confidence: 99%
“…Although effective vaccines are commercially available, CD is still an important infectious disease in dogs and wild carnivores [ 24 , 25 , 32 ]. In many cases, progression of the disease may differ depending on factors such as the rearing environment, virus strain, age, and immune status of the individual [ 3 , 17 ].…”
mentioning
confidence: 99%